Complete mitochondrial genome of the feather mite Ardeacarus ardeae (Acari, Sarcoptiformes, Pterolichidae) - Yeong-Deok Han; Gi-Sik Min (Mitochondrial DNA. Part B. Resources, 2017)
In this study, we determined the mitogenome sequence of Ardeacarus ardeae (Canestrini, 1878) in the family Pterolichidae (Acari, Sarcoptiformes), which is the first complete mitogenome sequence in feather mite. The mitogenome of A. ardeae is 14,069 bp in length and contains 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs), and a control region (CR). The phylogenetic tree shows that A. ardeae belong to the supercohort Desmonomatides within the order Sarcoptiformes.